5,8-Dimethoxy-3,9-dimethyl-3a,4,9,9a-tetrahydro-4,9-epoxynaphtho[2,3-d]isoxazole - Lough, Alan J. (International Union of Crystallography, 2014)
The title compound, C(15)H(17)NO(4), is the exo isomer with a syn arrangement of the O atom in the isoxazole ring to the methyl group of the bicyclic alkene. The dihedral angle between the isoxazole ring and the benzene ring is 7.42 (9)°. In the crystal, weak C—H⋯O hydrogen bonds link molecules, forming a three-dimensional network. The isoxazole O atom is an acceptor for both weak hydrogen bonds.